Bacteriophage-Resistant Mutant of Enterococcus faecalis Is Impaired in Biofilm Formation - Liu, Jiazhen; Zhu, Yanpeng; Li, Yang; Lu, Yuwen; Xiong, Kun; Zhong, Qiu; Wang, Jing (Frontiers in Microbiology, 2022)
Enterococcus faecalis is a common gram-positive non-spore-forming bacterium in nature and is found in the upper respiratory tract, intestine, and mouth of healthy people. E. faecalis is also one of the common pathogens causing nosocomial infections and is resistant to several antibiotics commonly used in practice. Thus, treating drug-resistant E. faecalis with antibiotics is challenging, and new approaches are needed. In this study, we isolated a bacteriophage named EFap02 that targets E. faecalis strain EFa02 from sewage at Southwest Hospital. Phage EFap02 belongs to the Siphoviridae family with a long tail of approximately 210 nm, and EFap02 can tolerate a strong acid and alkali environment and high temperature. Its receptor was identified as the capsular polysaccharide. Phage-resistant mutants had loss-of-function mutations in glycosyltransferase (gtr2), which is responsible for capsular polysaccharide biosynthesis, and this caused the loss of capsular polysaccharide and interruption of phage adsorption. Although phage-resistant mutants against EFap02 can be selected, such mutants are impaired in biofilm formation due to the loss of capsular polysaccharide, which compromises its virulence. Therefore, this study provided a detailed description of the E. faecalis EFap02 phage with the potential for treating E. faecalis infection.